PENGARUH HARGA TERHADAP KEPUTUSAN KONSUMEN MEMBELI RUMAH TIPE 36 PADACV. PERDANA LAJU MANDIRI DI GUNTUNG MANGGIS KOTA BANJARBARU - Jumiati; Emilia (Fekon Uvaya Banjarmasin, 2017)
This study aims to determine and prove that prices affect the consumer's decision to buy the house of type 36 in the CV. Prime rate of Mandiri in Manggis Guntung Banjarbaru.There are two variables in this study, the independent variable (Independent) are denoted by X, namely types 36 house prices on the CV. Prime rate Mandiri and the dependentvariable (Dependent) represented by Y is the consumer's decision to buy a house type 36 CV. Prime rate Mandiri. Number pupulasi in this study was 50 and made the overall sample of 50 respondents. Sampling using simple random sampling (simplerandom sampling). To determine whether there is the influence of the independentmvariable (X) to the dependent variable (Y) used simple regression analysis model equationY'= -1.287 + 0,982X. The conclusion of this study is t test showed that t count> t tablemwhere thitung 9.801> 2.011 ttabel. This means that the independent variable (X) there isma positive and significant effect on the dependent variable (Y). The coefficient ofmdetermination shows the figure of 0.667 which means that the price variable (X) has a contribution of 66.7% of the consumer decision variable(Y), while the remaining 33.3% is influenced by other variables not examined in this study.